(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This article discusses the prospects of tourism in the world economy, its place in socio-economic development, practical aspects of its importance and development, and the need to scientifically research its theoretical and methodological foundations. In their research, world scientists focus on clarifying the essence of the concept of "recreational tourism".